Análise de risco considerando a segurança nuclear e proteção física de uma instalação nuclear hipotética - Abreu, Caio Coqueijo de (2018)
Following the September 11 attacks on US twin towers, several countries on the European continent have become targets of numerous terrorist attacks. Following these recurring incidents, a major concern with events that are a major consequence of life and security have become a major focus in politics. Due to the evolution of threats of terrorism to the world powers, it has been necessary to acquire safely, especially in facilities that use nuclear materials. This work focuses on the analysis of components of an emergency system and a vulnerability of the physical protection systems of the nuclear installation. The degree of analysis will be analyzed through the probabilities of failure and unavailability of the components. A vulnerability of the physical protection system by controlling the probability of interruption and neutralization. A methodology used for the combination of safety and security is through fault trees with frequency of events. The results will evidence the degree of threat and risk of sabotage of the nuclear facility, the importance of combining physical protection analysis when its efficiency in deterring an adversary and probabilistic analysis of systems. The allocation of resources to the physical protection systems will be the result of an efficient probabilistic analysis of the systems